Effect of cultar, potassium and salinity of irrigation water on some characteristics of vegetative growth of two cultivars of apricot (Prunus armeniaca L.) (Baghdad Science Journal, 2011)
This experiment was conducted in the orchard of the Department of Horticulture,college of Agriculture,Baghdad University during the growing season of 2007 To study the effects of spray with three concentration of cultar(0,500,1000 mg.L-1) ,tow concentration of K2SO4(0,5g.L-1), and salinity of irrigation water with three concentration (1,2,3dS.m-1) on some characteristics of vegetative growth of two cultivars of apricot trees (Labib1 and Zienni).The age of trees was four years .The tree grafted on original of seed apricot . Afactorial trail was carry out according to randomized complete block design with arrangement of split-split with three replications. Salinity of irrigation water took main plot, potassium took sub plot and cultar took sub sub plot, cultar significantly reduced the plant height and leaves area at apercentage of( 26.77 , 24.1 and 12.33 , 15.95%) respectively in labib and zienny cultivars respectively. Weheras significantly increased carbohydrates at apercentage of (4.44,4.35%) in labib and zienny cultivars respectively. K2SO4 was significantly increased the plant hight, leaves area and carbohydrates at apercentage of (15.66,12.82, 10.36,9.10 and 2.61,2.15%) respectively in labib and zienny cultivars respectively. Irrigation water salinity was decreased the plant hight, leaves area and carbohydrates at apercentage of (25.69, 29.17,15.29,16.29 and 24.31,30.65%) respectively in labib and zienny cultivars respectively.